Weakly Stable Regions and Protein-Protein Interactions in Beta-Barrel Membrane Proteins - Naveed, Hammad (2014)
We briefly discuss recent progress in computational characterization of the sequence and structural properties of β-barrel membrane properties. We discuss the emerging concept of weakly stable regions in β-barrel membrane proteins, computational methods to identify these regions and mechanisms adopted by β-barrel membrane proteins in nature to stabilize them. We further discuss computational methods to identify protein-protein interactions in β-barrel membrane proteins and recent experimental studies that aim at altering the biophysical properties including oligomerization state and stability of β-barrel membrane proteins based on the emerging organization principles of these proteins from recent computational studies.